Small island mitigation based on mangrove ecosystem management in Bunaken National Park - Schaduw, Joshian N.W (AQUATIC SCIENCE & MANAGEMENT, 2013)
Small islands are susceptible to many environmental impacts. Impacts affecting ecological processes include climate change, sea level rise, natural disasters, abrasion, sedimentation, erosion and pollution. To minimize vulnerability the assessing the effectiveness of mitigation measures in these coastal ecosystems is urgently needed. This research analyzes vulnerability of a small island mangrove ecosystem and the effectiveness of management strategy for mangrove ecosystem based mitigation. This research uses both primary and secondary data. Primary data was gathered by sampling, field observation, and questionnaire analysis. Vulnerability index was analyzed using multi-dimensional scaling method, and vulnerability mapping was analyzed by using geographic information system (GIS) using the software Arcview Project 3.3. Stakeholder analysis was used for patterns and strategic management, through a technique SMART (Simple Multi Attribute Rating Technique) using the software Criterium Decision Plus. The results show that Bunaken Island has the highest vulnerability level, followed by the island of Manado Tua, Nain, and the lowest level was found in Mantehage island. The most important factor of vulnerability in the small island Bunaken National Park is the area of mangrove ecosystem. Increased area of mangrove ecosystem will increase the effectiveness as a buffer zone as well as increase the capacity of the ecosystem on the social, economic, and governance dimensions. A management scheme which can accommodate a variety of problems faced by the mangrove ecosystem of small islands is a collaborative management by the government as the leading sector, with the highest priority on the management of the ecological dimension.Â Pulau-pulau kecil merupakan daerah yang rentan terhadap berbagai faktor. Salah satu faktor yang mempengaruhi adalah faktor ekologis. Faktor ekologi meliputi perubahan iklim, kenaikan permukaan air laut, bencana alam, abrasi, sedimentasi, erosi dan polusi. Untuk meminimalkan kerentanan, efektivitas ekosistem pesisir sangat dibutuhkan. Penelitian ini menganalisis kerentanan pulau kecil, efektivitas ekosistem mangrove, dan strategi pengelolaan ekosistem mangrove berbasis mitigasi. Penelitian ini menggunakan data primer dan sekunder. Data primer dikumpulkan melalui sampling, observasi lapangan, dan angket. Kerentanan dianalisis menggunakan metode multidimensional scaling, sedangkan pemetaan kerentanan dianalisis dengan sistem informasi geografis menggunakan perangkat lunak ArcView 3.3. Analisis Stakeholder digunakan untuk pola dan manajemen strategi, melalui teknik SMART (Simple atribut teknik Peringkat multi) dengan menggunakan perangkat lunak Criterium Decision Plus. Hasil penelitian menunjukkan Pulau Bunaken memiliki tingkat kerentanan tertinggi, diikuti oleh Pulau Manado Tua, Nain, dan Pulau Mantehage terendah. Faktor utama kerentanan di pulau kecil Taman Nasional Bunaken adalah luasan ekosistem mangrove. Peningkatan kawasan ekosistem mangrove akan meningkatkan efektivitas ekosistem mangrove sebagai buffer zone serta meningkatkan kapasitas ekosistem ini pada dimensi sosial, ekonomi, dan pemerintahan. Pola pengelolaan yang dapat menampung berbagai masalah yang dihadapi oleh ekosistem mangrove pulau-pulau kecil adalah kolaboratif manajemen dengan prioritas utam pada pengelolaan dimensi ekologi dan pemerintah sebagai leading sector.